Kedudukan Akta Perdamaian dalam Penanganan dan Penyelesaian Kasus Pertanahan - Mahardhika, Elgha Kusuma; Masykur, M. Hamidi; Supriyadi, Supriyadi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 3 (2024), 2024)
Article 28 D paragraph (1) of the 1945 Constitution of the Republic of Indonesia is the basis for the implementation of legal protection in Indonesia, including in terms of holding land mediation which is regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning Number 21 of 2020 concerning Handling and Settlement Land Cases. In this article, the author's aim is to review the provisions of mediation, especially regarding the position of the peace deed in the Ministerial Regulation in terms of the concept of mediation in Indonesia which is regulated in the Civil Code, HIR and supreme court regulations. The first result of the research in this paper is that the Peace Deed, although not explicitly required, needs to be registered with the court in order to obtain a Peace Decision as a requirement for administrative recording at the National Land Agency. Meanwhile, secondly, the technical mediation in the Ministerial Regulation is in line with the concept of mediation which is generally applied referring to the Civil Code, HIR and supreme court regulations